ANALISIS KEUNTUNGAN USAHA WARUNG MAKAN DI PASAR SANGGAM ADJI DILAYAS KABUPATEN BERAU - Rian Hidayat; Reza Reza; Kadori Haidar; Noor Ellyawati (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
This study aims to determine (1) how much profit is earned and (2) the business location of the food stall based on the type of food produced at the Warung Makan at the Sanggam Adji Dilayas Market, Berau Regency. The type of research used is descriptive quantitative. This study uses data collection in the form of observation, interviews, documentation, and questionnaires. The results showed that the Grilled Fish food group had the highest level of profit among other food groups, which was Rp. 36,220,549 per month, and the Soto food group has a level of excellence among other food groups, which is Rp. 5,289,676 per month, and located right by food group, and Ikan Bakar has the highest ratio of other food groups, which is 2.0 and Nasi Campur has the smallest ratio among other groups, which is 1.2. So the conclusion of this study is that of the seven food groups selected, each has an interest and is in accordance with the selected group, according to the food group produced or sold by each food group that is appropriate and in accordance with their respective needs. to run and develop         Keywords: Reception, Production Cost, Profit, Business Feasibility